Deriving Improvement Plans through Metaverse Technology and Implications - Hyun, Jeonghee; Choi, Hanyong; Kim, Jaesaeng (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Metaverse-based technology and its service area become wider through online environment and virtual reality. In the Metaverse space where the virtual I and another virtual person can interact each other in the virtual reality, we are already playing games and performing education and presentation, etc.. To enable such VR activities, converged ICT technology is needed. Something in common between Metaverse and Virtual reality is to experience in the VR environment. The main characteristic of virtual reality is the experience in the perspective of first person and that of the Metaverse is that there is interaction each other in the perspective of diverse persons. As it is being extended to X-Metaverse where the boundary of Metaverse disappears expanding to diverse fields, in this paper, it is intended to suggest ideal Metaverse construction method and improvements through major technologies and characteristics in building X-Metaverse and diverse application fields and cases.